Analisis Kelayakan Usahatani Pembibitan Alpukat Cipedak - Edwin Kawilarang; Yusuf Muhyiddin; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Fruits are horticultural commodities that have a major contribution to agriculture in Indonesia. One of them is horticultural crops, namely avocado plants. Avocado has the Latin name Persea Americana Mill. Avocados are one of the horticultural commodities that have high economic value. In the Sejahtera Makmur farmer group, they carry out breeding activities for the original variety of avocado from South Jakarta, namely the Cipedak avocado. This study aims to analyze the costs (fixed and variable), income, farm income and the financial feasibility of Cipedak avocado seeds. The research method used is a quantitative research approach by conducting survey techniques. Primary data was collected by distributing questionnaires, structured interviews and observation. The respondents of this study were all members of the Makmur Makmur Sejahtera farmer group, which consisted of 10 nursery farmers. All production activities are carried out in one area of 800 m2 and all costs and benefits are shared. The analysis technique used is Revenue Cost Ratio and Break Even Point. The results obtained that the average Cipedak Avocado seedling from January to June has an average total production cost of Rp. 20,997,515/season and an average total income of Rp. 60,000,000/planting season. So the average income is Rp. 39,002,485/season with a land area of 1,000 m2. So it can be concluded, Cipedak avocado seed farming at the Sejahtera Makmur farmer group, Ciganjur Village is feasible from a financial point of view and this business is profitable. In addition, an R/C value of 2.85 > 1 was obtained, with the interpretation that Cipedak avocado seed farming was profitable and feasible to cultivate. Based on the calculation of the Break Even Point or the break-even point, the production BEP is 524.93 seeds and the BEP is Rp. 13,998/seed. So it can be concluded that the Cipedak avocado nursery farm in the Sejahtera Makmur farmer group has more value than the break-even point, which is getting profit and is feasible to cultivate